Use of Calixarenes Bearing Benzoyl Groups for the Adsorption of Heavy Metals Cations: Equilibrium and Kinetics Studies (Universitas Jenderal Soedirman, 2023)
This study aims to examine the potential of p-tert-butylkalix[4]arene derivatives, namely 5,11,17,23-tetra-tert-butyl-25,26,27,28-tetrahydroxy-calix[4]arene (TBCA), and 5,11,17,23-tetra-tert-butyl-25-monohydroxy-26,27,28-tribenzoyloxycalix[4]arene (TBMTCA) as adsorbent for metal cations, such as Pb(II) and Fe(III). The synthesized compounds were characterized using FT-IR and 1H-NMR spectroscopy. The adsorption studies were then carried out with contact time as a parameter, while the kinetics were evaluated using the Lagergren and Ho-McKay equations. The isotherms were analyzed using the Langmuir and Freundlich equations. For the kinetics of TBCA adsorbents, Pb(II) cations followed the Ho-McKay model, while Fe(III) was based on Lagergren. Furthermore, for the TBMTCA adsorbent, Pb(II) followed the Lagergren kinetic model, while Fe(III) was based on the Ho-McKay. The cation adsorption isotherms of Pb(II)-TBCA, Pb(II)-TBMTCA, Fe(III)-TBCA, and Fe(III)-TBMTCA are more in line with the Langmuir model. These results indicate that they can be used as heavy metal adsorbents, and recycled to increase their economic value.